Characterization of neurocognitive deficits in patients with post-COVID-19 syndrome: persistence, patients’ complaints, and clinical predictors - Kozik, Valeska; Reuken, Philipp; Utech, Isabelle; Gramlich, Judith; Stallmach, Zoe; Demeyere, Nele; Rakers, Florian; Schwab, Matthias; Stallmach, Andreas; Finke, Kathrin (Frontiers in Psychology, 2023)
Introduction Cognitive symptoms persisting beyond 3 months following COVID-19 present a considerable disease burden. We aimed to establish a domain-specific cognitive profile of post-COVID-19 syndrome (PCS). We examined the deficits’ persistence, relationships with subjective cognitive complaints, and clinical variables, to identify the most relevant cognitive deficits and their predictors. Methods This cross-sectional study examined cognitive performance and patient-reported and clinical predictors of cognitive deficits in PCS patients (n = 282) and socio-demographically comparable healthy controls (n = 52). Results On the Oxford Cognitive Screen-Plus, the patient group scored significantly lower in delayed verbal memory, attention, and executive functioning than the healthy group. In each affected domain, 10 to 20% of patients performed more than 1.5 SD below the control mean. Delayed memory was particularly affected, with a small effect of hospitalization and age. Attention scores were predicted by hospitalization and fatigue. Discussion Thus, PCS is associated with long-term cognitive dysfunction, particularly in delayed memory, attention, and executive functioning. Memory deficits seem to be of particular relevance to patients’ experience of subjective impairment. Hospitalization, fatigue, and age seem to predict cognitive deficits, while time since infection, depression, and pre-existing conditions do not.